Dilema Izin Perkebunan di Koridor Gajah Sumatra: Tinjauan Yuridis Penegakan Hukum Ekosistem Terfragmentasi di Lansekap Bukit Tigapuluh, Jambi. - Rayi Kharisma Rajib; Priskila Dwita Yoan Veda (JURNAL ILMIAH NUSANTARA, 2026)
This study analyzes the legal dilemma between granting plantation permits and protecting the Sumatran Elephant corridor in the increasingly fragmented Bukit Tigapuluh Landscape. The main problem lies in the mismatch between environmental impact assessment (Amdal) data and wildlife migration routes, causing business permits to often be issued over critical ecosystems. The study results indicate that law enforcement remains administrative in nature and has not been able to compel companies to restore disrupted corridors. Therefore, integrating habitat maps into the permitting system and strengthening restorative sanctions are needed to ensure the conservation of elephants in Jambi Province.